SCREENING APPROACHES FOR METHANE MITIGATING POTENTIAL OF TANNIN-CONTAINING PLANTS UNDER IN VITRO RUMEN ENVIRONMENT - Jayanegara, A.; Ridla, M.; Nahrowi, N. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The aim of the present study was to conduct univariate, bivariate and multivariate (principalcomponent analysis, PCA) approaches in the screening of tannin-containing plants from variouscollection sites for their CH4 mitigating properties. Plant samples were obtained from various collectionsites in different countries, i.e. Indonesia (n = 27 species), Mongolia (n = 14), Switzerland (n = 16) andGermany (n = 3). The plants were incubated in vitro with buffered-rumen fluid at 39oC for 24 h. Totalgas production was recorded as an indicator of feed quality and emission of CH4 was measured. Resultsshowed that, based on bivariate screening, generally, plants possessed low CH4 production had lowquality or low total gas production except Rhus typhina, i.e. 43 ml/200 mg DM. The loading plot of PCAshowed that all phenolic fractions were in the opposite direction with CH4 and total gas production.Plants clustered together in reverse direction to that of CH4 were Bergenia crassifolia root and leaf,Swietenia mahagoni, Clidemia hirta, Peltiphyllum peltatum, Acacia villosa and R. typhina. It wasconluded that, for tannin-containing plants, screenings based on univariate, bivariate and multivariateapproaches in relation to ruminal CH4 emission led to similar results.